2019
DOI: 10.14720/aas.2019.114.2.1
|View full text |Cite
|
Sign up to set email alerts
|

Extent and financial cost of cassava postharvest loss along the cassava value chain in Kwara State, Nigeria

Abstract: Extent and financial cost of cassava postharvest loss along the cassava value chain in Kwara State, NigeriaAbstract: Cassava has been identified as Africa's second most important staple food after maize, in terms of calories consumed, with Nigeria as the World leading producer. This study estimated postharvest loss of cassava along the cassava value chain in Kwara State. It estimated the size of postharvest loss of cassava; analysed the factors responsible and the financial implications of loss; and identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
1
2
0
Order By: Relevance
“…Uchemba et al (2021) reported that education has a great influence on the adoption of agricultural technology. This is also in line with the report of Temitope et al (2019) who reported that most of their respondents spent 7 -12 years in school. Again, 41.7% of the farmers have been in the business of cassava production for the past 1-10 years, 37.5% spent 11 -20 years of cassava production experience and 20.8% had 20 years (21 years and above) experience in the business of cassava production.…”
Section: Socioeconomic Characteristics Of Cassava Farmerssupporting
confidence: 92%
See 1 more Smart Citation
“…Uchemba et al (2021) reported that education has a great influence on the adoption of agricultural technology. This is also in line with the report of Temitope et al (2019) who reported that most of their respondents spent 7 -12 years in school. Again, 41.7% of the farmers have been in the business of cassava production for the past 1-10 years, 37.5% spent 11 -20 years of cassava production experience and 20.8% had 20 years (21 years and above) experience in the business of cassava production.…”
Section: Socioeconomic Characteristics Of Cassava Farmerssupporting
confidence: 92%
“…Its ability to produce high yields under poor conditions and storage of its harvestable portion underground until when needed, gives it an edge. This has made it a classic` food security crop` and encourage its cultivation by a resource-poor farmer (Temitope, Babatunde and Animashaun (2019). In addition, the starchy roots produce more food energy than any other staple crop, and accounts for about 70% of the total calorie intake of more than half of Nigerians (Nweke and Enete, 1999).…”
Section: Introductionmentioning
confidence: 99%
“…Data collected were analyzed using descriptive statistics, Shannon's diversity index(Avilez-López et al, 2020; Danilola et al, 2019;Konopiński, 2020), and Tobit regression model (Ding et al, 2017;Jassam et al, 2022;Kumari et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Its ability to produce high yields under poor conditions and underground storage of its harvestable portion until needed gives it an edge. This has made it a classic` food security crop` and encouraged its cultivation by resource-poor farmers (Danilola et al, 2019). In addition, starchy roots produce more food energy than any other staple crop and account for about 70% of the total calorie intake of more than half of Nigerians.…”
Section: Introductionmentioning
confidence: 99%
“…Coupled with this is high perishability of cassava (Kwasi & Kobina, 2014). The economic cost of cassava loss is $300ha-1 (Danilola et al, 2019).…”
Section: Introductionmentioning
confidence: 99%